Mediating effect of government policy on the relationship between key internationalisation factors and Malaysian higher education institutions’ internationalisation performance - Daud, Nureezan (2019)
In light of the increased globalisation and rapid transformation of the higher education sector, countries and HEIs were forced to address the challenges of global higher education in order to build their reputation, compete and sustain at the global level. One of the effective and pertinent strategies to enhance the higher education institutions internationalisation performance is to attract more international students into the country. In this regard, the current study is designed to determine the key factors that profoundly influence Malaysian HEIS’ internationalisation performance. This study also focused on investigating the relationships between financial conditions, marketing strategies, HEIs’ reputation, and HEIs’ international student management towards government policy and Malaysian HEIs’ internationalisation performance. The relationship between government policy and the Malaysian HEIs’ internationalisation performance was also examined. The mediating role of government policy on the relationships between the variables namely, financial conditions, marketing strategies, HEIs’ reputation and HEIs’ international students' management and the Malaysian HEIs’ internationalisation performance were also studied. The current study adopted a non-probability sampling survey method involving convenience sampling and snowball sampling to answer the research questions that have been developed. Results of the study proved that financial conditions, marketing strategies, HEIs’ reputation and HEIs’ international student management had significant relationship towards the Malaysian HEIs’ internationalisation performance. Results of the study also showed that, except for marketing strategies, all other independent variables, including financial conditions, HEIs’ reputation and HEIs’ international student management had significant relationship towards government policy. Results also proved that government policy is significantly related to Malaysian HEIs’ internationalisation performance. Finally, results also indicated that government policy strongly mediated the relationships between financial conditions, marketing strategies, HEIs’ reputation, and HEIs’ international student management with Malaysian HEIs’ internationalisation performance. However, as this study uses the convenience sampling method, the findings may not be appropriate to be generalised to all population of international students studying in Malaysia. The current study’s research framework highlights the importance of considering the identified influential key factors of Malaysian HEIs’ internationalisation performance, for Malaysian HEIs to design and implement their internationalisation strategies effectively. The findings of this study are also pertinent for policymakers of higher education in designing, executing and enhancing higher education policies conducive for Malaysia to achieve the target to become the international hub of educational excellence in the year 2025.